2017
DOI: 10.1111/jcmm.13402
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CPPED1 in human trophoblasts is associated with timing of term birth

Abstract: Understanding of timing of human parturition is incomplete. Therefore, we carried out proteomic analyses of full‐term placentas from uncomplicated pregnancies to identify protein signatures associated with the onset of spontaneous delivery. We found quantitative associations of 10 proteins with spontaneous term birth, evident either in the basal or in the chorionic plates or in both. Additional 18 proteins were associated according to the location within placenta indicating local variations in protein amounts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 62 publications
(85 reference statements)
1
37
0
Order By: Relevance
“…A recent analysis investigated SNVs (n = 77) in ten fetal genes encoding placental proteins associated with the duration of pregnancy. Of these, only a SNV within CPPED1 associated with pregnancy duration (71). Both CPPED1 protein and CPPED1 mRNA in the basal plate of the placenta were associated with labor and length of pregnancy.…”
Section: Gwas Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent analysis investigated SNVs (n = 77) in ten fetal genes encoding placental proteins associated with the duration of pregnancy. Of these, only a SNV within CPPED1 associated with pregnancy duration (71). Both CPPED1 protein and CPPED1 mRNA in the basal plate of the placenta were associated with labor and length of pregnancy.…”
Section: Gwas Studiesmentioning
confidence: 96%
“…CPPED1 is a phosphatase that inactivates AKT1 in the PI3K/AKT1 signaling pathway in bladder cancer cells (72). A pathway analysis in which siRNA was used to inhibit CPPED1 expression in trophoblastderived cells revealed that CPPED1 affects expression of genes involved in angiogenesis and proximal PI3K/AKT1 signaling pathways (71). Potential phosphorylation targets of AKT1 include inactivation of hypo phosphorylated FOXO1, which participates in the progesterone receptor B (PR-B) transcriptional complex (73).…”
Section: Gwas Studiesmentioning
confidence: 99%
“…previously [23,39]. Briefly, qPCR was done as an intron-spanning assay with the LightCy-cler196 (Roche).…”
Section: Plos Onementioning
confidence: 99%
“…We showed previously that expression levels of calcineurin like phosphoesterase domain containing protein 1 (CPPED1) are associated with timing of birth and that spontaneous term placentas have decreased levels of CPPED1 compared to elective term placentas of deliveries without signs or symptoms of labor [23]. Additionally, expression of CPPED1 is decreased in invasive bladder cancer and overexpression of CPPED1 delays progression of the cell cycle [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation